Fish health status, research and management in East Africa: past and present - Akoll, P.; Mwanja, W. W. (African Journal of Aquatic Science, 2012)
This paper reviews the state of research on fish pathogens in Burundi, Kenya, Rwanda, Tanzania and Uganda from the early 1900s, the period when fisheries management started in the region, to date, and evaluates the current policy, regulatory frameworks, management practices and frameworks for addressing fish health issues in East African Community countries. Host pathogens and their distributions are listed. To date, fish health research has focused on the occurrence and taxonomy of parasites mainly in wild hosts. Very limited research output and knowledge exist on bacterial, viral and fungal disease agents and on fish culture systems, as well as on parasites’ life cycles and/or vectors, epidemiology, pathogenicity, prevention and control. The current fish disease control and preventive strategies and diagnostic facilities are basic and non-specific. Although the five countries have legislation for the management of fisheries that clearly mention the restriction of movement of fish and fish products, they lack comprehensive policy and regulatory provisions to ensure an appreciable level of disease prevention and control. With the intensifying fish farming in the region, the research gaps in fish pathology, the potential impacts of the pathogens and the lack of appropriate management framework for fish diseases highlight the need to strengthen aquatic biosecurity.
Keywords: Aquaculture; Aquatic health management; Disease; East African Community